2014
DOI: 10.2172/1171351
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Outdoor Temperature-Based Control Algorithm for Residential Mechanical Ventilation Control

Abstract: Executive SummarySmart ventilation systems use controls to ventilate more during those periods that provide either an energy or IAQ advantage (or both) and less during periods that provide a disadvantage. Using detailed building simulations, this study addresses one of the simplest and lowest cost types of smart controllers-outdoor temperature-based control. If the outdoor temperature falls below a certain cut-off, the fan is simply turned off. The main principle of smart ventilation used in this study is to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…So, the system was effectively able to control to seven discrete hourly average mechanical ventilation rates, from 0 to 300% of 62.2-2013, by 50% increments (each representing 10-minutes of runtime in the hour). As was found by Less et al (2014), larger ventilation fans increase the ability to engage in smart control strategies, while maintaining annual equivalence. For this reason, the CFIS system provides an excellent opportunity for smart ventilation control, though its energy use is typically greater due to use of the central air handler fan for distribution.…”
Section: Fan Sizing Considerationsmentioning
confidence: 60%
See 1 more Smart Citation
“…So, the system was effectively able to control to seven discrete hourly average mechanical ventilation rates, from 0 to 300% of 62.2-2013, by 50% increments (each representing 10-minutes of runtime in the hour). As was found by Less et al (2014), larger ventilation fans increase the ability to engage in smart control strategies, while maintaining annual equivalence. For this reason, the CFIS system provides an excellent opportunity for smart ventilation control, though its energy use is typically greater due to use of the central air handler fan for distribution.…”
Section: Fan Sizing Considerationsmentioning
confidence: 60%
“…Acceptable IAQ is defined as providing annual pollutant exposure equivalent to a continuously operated ventilation fan sized to ASHRAE Standard 62.2-2013. Smart ventilation strategies have been previously applied to energy conservation and peak demand reduction using time-based controls as well as sensors for other ventilation fans (Max H. Sherman & Walker, 2011), and based on indoor/outdoor temperatures (Less, Walker, & Tang, 2014). The same principles will be applied in this study for humidity control.…”
Section: Rhmentioning
confidence: 99%
“…It may be possible to achieve greater energy savings if an additional level of complexity is added onto the Seasonal control. Past work on temperature-controlled smart ventilation suggested that a simple cut-off temperature was an effective approach to reducing ventilation load through smart control (Less et al, 2014). In this work, we developed a cut-off approach that ensures annual relative exposure less than one using a weighted average approach.…”
Section: Cut-off Temperature Control (Cutoff)mentioning
confidence: 99%
“…Past work on temperature controlled smart ventilation suggested that a simple cut-off temperature was an effective approach to reducing ventilation load through smart control (Less et al, 2014). In this work, we developed a more complicated cut-off approach that ensures annual relative exposure less than one using a weighted average approach and parametric optimization (as in the Seasonal controller).…”
Section: Appendix D Cut-off Temperature Control (Cutoff) Control Descmentioning
confidence: 99%
See 1 more Smart Citation